Model Collaborative Governance Penataan Kawasan Wisata - Bambang Rudiansah (Jurnal Kajian Ilmiah, 2024)
Collaborative Governance in managing the Anyar Tourism Village in Laksana Village, Ibun District, Bandung Regency is carried out through collaboration between the regional government, local communities and various existing policy stakeholders to manage tourism destinations together, this allows for active participation from the community to take part. decisions, resource management and infrastructure development. This research uses a descriptive qualitative method which aims to find out how to optimize the implementation of collaborative governance by using data sources through interviews, observation and documentation, and using secondary data sources since 2023. The research results obtained in Collaborative Governance in the management of the Laksana Tirta Tourism Village Newly, each actor plays a different role. The Laksana Village Government and private parties who participate in the management of the Laksana Tirta Anyar Tourism Village act as facilitators in supporting the management of the Laksana Tirta Anyar Tourism Village. The Laksana Village Government plays a role by providing legal permits. The Laksana Government also carries out its role as a facilitator by making regulations regarding the utilization of village fund assets through BumDesa as well as being a bridge between the Government and the Private Sector. Then the Laksana Government is also a stakeholder in every program for the development of the Tirta Anyar Tourism Village.